2003
DOI: 10.2134/jeq2003.1173
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Ammonia, Volatile Fatty Acids, and Other Odorants near Beef Feedlots

Abstract: Intensive livestock operations can release odorous gases from stored or land-applied manure. We measured concentrations of dust and 14 odor-causing gases at increasing distances from four feedlots near Lethbridge, southern Alberta, Canada. Concentration was determined from the amount of total dust or gas accumulated in the sampIers, and the volume of air sampled. Adjacent the feedlots, the maximum concentration of many volatile fatty acids exceeded reported odor detection thresholds; the maximum ammonia concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 31 publications
4
58
0
Order By: Relevance
“…However, it should be noted that peak concentrations, 1936.7 mg m À3 , were well below NIOSH recommended eight hour exposure levels of 25,000 mg m À3 (NIOSH, 2005). However, average concentrations of acetic acid reported in this study were well above what has been reported for other animal groups (Zahn et al, 1997(Zahn et al, , 2001McGinn et al, 2003;Ngwabie et al, 2008). Currently most studies on workers occupational health risks from poultry facilities have focused exclusively on inhalation of dust or bioaerosols, but this study would suggest that some attention should also be paid to the role VOCs may play on worker respiratory health.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…However, it should be noted that peak concentrations, 1936.7 mg m À3 , were well below NIOSH recommended eight hour exposure levels of 25,000 mg m À3 (NIOSH, 2005). However, average concentrations of acetic acid reported in this study were well above what has been reported for other animal groups (Zahn et al, 1997(Zahn et al, , 2001McGinn et al, 2003;Ngwabie et al, 2008). Currently most studies on workers occupational health risks from poultry facilities have focused exclusively on inhalation of dust or bioaerosols, but this study would suggest that some attention should also be paid to the role VOCs may play on worker respiratory health.…”
Section: Resultssupporting
confidence: 56%
“…In terms of VOC speciation, it was not surprising that alcohols, ketones, and VFAs were the most abundant chemical classes since these compounds have been shown to be abundant with other animal groups (Zahn et al, 2001;McGinn et al, 2003;Blunden et al, 2005;Filipy et al, 2006;Ngwabie et al, 2008) and previous studies with poultry litter/manure have also reported the significance of these chemical classes (Smith et al, 1977;Yasuhara, 1987). Odor studies from poultry litter/manure have reported the significance of both 2,3-butanedione, 3-hydroxyl-2-butanone and carboxylic acids (Burnett, 1969;Cai et al, 2007).…”
Section: Resultsmentioning
confidence: 98%
“…Agricultural activity is another primary emission source of alkanoic acids (McGinn et al, 2003;Paulot et al, 2011), and may have contributed to the observed alkanoic acid mixing ratios. NH 3 in the Colorado Front Range comes primarily from agricultural sources (Tevlin et al, 2017).…”
Section: Alkanoic Acidsmentioning
confidence: 99%
“…Another contentious issue with fresh manure is odour emissions during land application (McGinn et al 2003). One of the benefits most often espoused for land application of compost, compared with fresh manure, is that it is virtually odourless.…”
Section: Elimination Of Undesirablementioning
confidence: 99%